OPERATIONS OF THE CENTRAL BANK ON THE FINANCIAL MARKET FOR THE PERIOD OF EXIT FROM THE RECESSION - O. Liubkina (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The global economy is currently facing one of the longest recessions in the past fifty years. The way out of the Great recession requires active measures to stimulate the demand in the economy. However, distinctive features of the recent recession are the significant amount of a debt burden on national budgets, low inflation contributes to an increasing potential of a monetary policy to ensure economic recovery, but require from the central bank an unconventional approach to achieve the broad set of goals. One of the tools of so-called unconventional monetary policy is quantitative easing. The USA experience of applying the unconventional monetary policy suggests that the quantitative easing is an effective tool for warming up the economy in the recession phase, especially in the medium terms, but it causes challenges for developing of the national economy (credit risk deterioration of the central bank's portfolio, rising commodity prices, flows of speculative capital) and like "secondary effects" challenges for developing of the global economy (interest rates volatility, price bubbles on stock markets, currency risks, etc.).